EXPLOITATION OF HETEROSIS FOR BIOETHANOL PRODUCTION IN SWEET SORGHUM (SORGHUM BICOLOR L. MOENCH.) HYBRIDS - D. M. BAHADURE; S. MARKER; A.V. UMAKANTH; PRABHAKAR; J. V. PATIL; G. J. SYNEREM (The Bioscan, 2014)
A study was conducted in sweet sorghum to estimate the magnitude of heterosis for bio-ethanol and biomass yield, thirty F1 hybrids derived from five Lines x Six testers cross combinations were evaluated in kharif 2012 along with their parents and check (CSH 22 SS) for heterosis to identify promising hybrids of sweet sorghum for bioethanol characters at three different locations viz: Allahabad (E1), Solapur (E2) and Hyderabad (E3). Heterosis over mid parent, better parent and standard check were studied for bio-ethanol and biomass yield traits. Hybrid NSS 1016 A x UK 81 had shown (354.10% and 282.52%), (507.94% and 365.94%), (306.81% and 214.79%) highest heterobeltiosis and economic heterosis in E1, E2 and E3 respectively. Whereas, for biomass yield trait, the hybrid NSS 8 A x SSV 84 had shown (251.14% and 186.40%), ICSA 675 X UK 81 (285.90% and 244.82% ) and PMS71A X SSV 84 (193.80% and 137.56% ) had shown highest heterobeltiosis and economic heterosis in environment E1, E2 and E3 respectively. These two hybrids were found to be promising hybrids for further breeding programme as they exhibited significant positive heterobeltiosis and economic heterosis for bio-ethanol and biomass yield related traits. Hence, it can be concluded that heterosis would be more reliable in identification and isolation of superior hybrids.